2019
DOI: 10.3389/fphar.2019.01351
|View full text |Cite
|
Sign up to set email alerts
|

C13 Megastigmane Derivatives From Epipremnum pinnatum: β-Damascenone Inhibits the Expression of Pro-Inflammatory Cytokines and Leukocyte Adhesion Molecules as Well as NF-κB Signaling

Abstract: In order to identify active constituents and to gain some information regarding their mode of action, extracts from leaves of Epipremnum pinnatum were tested for their ability to inhibit inflammatory gene expression in endothelial- and monocyte-like cells (HUVECtert and THP-1, respectively). Bioactivity-guided fractionation using expression of PTGS2 (COX-2) mRNA as a readout resulted in the isolation of two C13 megastigmane glycosides, gusanlungionoside C (1) and citroside A (3), and the phenylalcohol glycosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…NF-κB belongs to a family of transcription factors involved in the regulation of cell differentiation, proliferation PINCH1 knockout aggravates myocardial infarction in mice via mediating the NF-κB signaling pathway and apoptosis. As an inflammatory factor, NF-κB serves an important role in the immune system (11,12). Studies (13)(14)(15) have shown that the NF-κB signaling pathway is activated following MI and promotes ventricular remodeling in rats (16).…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB belongs to a family of transcription factors involved in the regulation of cell differentiation, proliferation PINCH1 knockout aggravates myocardial infarction in mice via mediating the NF-κB signaling pathway and apoptosis. As an inflammatory factor, NF-κB serves an important role in the immune system (11,12). Studies (13)(14)(15) have shown that the NF-κB signaling pathway is activated following MI and promotes ventricular remodeling in rats (16).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, glycosidic megastigmanes commonly have a 1″ → 6′ linkage in the disaccharide unit. The identification of 3 has been reported in a limited number of plant species [ 38 , 39 , 40 , 41 ] including Epipremnum pinnatum [ 42 ], which, like Colocasia , belongs to the Araceae family.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its low threshold (0.002 μg/L in water) and high odor activity value (OAV), β-damascenone has already been described having as baked/cooked apples, honey, and flowery fruity aromas in previous research ( Mendes-Pinto, 2009 ; Tomasino and Bolman, 2021 ). Furthermore, β-damascenone also exhibits interesting biological activities, including inhibition of the expression of proinflammatory cytokines and leukocyte adhesion molecules and the prevention of sunburn and skin cancer ( Uddin et al, 2012 ; Pan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%